(untitled) (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to examine marketing strategies and the development of Micro, Small, and Medium Enterprises (MSMEs) based on green innovation and sustainable business practices in the digital economy era. The research employs a literature review method using a qualitative approach and descriptive analysis. Data were collected from Google Scholar and various other credible publication sources, including ScienceDirect and ResearchGate, covering the period from 1991 to 2026. The initial search process identified 50 publications, which were subsequently screened based on relevance, source quality, and topic suitability, resulting in 37 articles selected for further analysis. Data analysis was carried out through a process of data reduction, categorisation of themes, interpretation of findings, and literature synthesis. The findings indicate that the integration of digital marketing, green innovation, and sustainable business practices can enhance competitiveness, operational efficiency, business reputation, and customer loyalty. The utilization of digital technologies expands market access, while green innovation and sustainability-oriented business practices create added value that is increasingly demanded by modern consumers. This review confirms that sustainability and digital transformation are strategic factors in developing competitive MSMEs with a long-term orientation. This study employed a literature review methodology; consequently, the findings are not yet directly supported by empirical data. Further research should adopt an empirical approach to examine the impact of marketing strategies, green innovation and business sustainability on the performance of MSMEs.